Consumers' interest and willingness to pay for traceable vegetables- An empirical evidence from Bangladesh - Kabir, A.N.M. Faijul; Alam, Mohammad Jahangir; Begum, Ismat Ara; McKenzie, Andrew M. (Elsevier, 2023)
Urban consumers’ concerns have focused attention on whether a food traceability system should be implemented in Bangladesh to minimize the production and distribution of unsafe and poor-quality food products. A cross-sectional survey was conducted among 220 consumers in two main cities Dhaka and Mymensingh of Bangladesh to examine the traceability system in the vegetable supply chain from an ex-ante perspective. The objective is to identify the preferences and willingness to pay (WTP) for the traceability attributes and examine the factors influencing their WTP for traceable vegetables. The results show that over 90% of the consumers put their emphasis on traceability attributes associated with: pesticides and last date of spraying information, fertilizer information, and harvest date. On the other hand, over 85% of consumers showed interest in GM information of vegetables. The mean WTP is found to be 5.84 Tk. (US$0.068) and 5.90 Tk. (US$0.069) per kg respectively for brinjal and tomatoes. This reflects a 19.5% and 19.7% additional monetary payment over and above the purchase price for conventional brinjal and tomatoes respectively. The empirical findings indicate that income and quality perception scores have positive and significant effects on consumer WTP for traceable brinjal and tomatoes.